Ranking Prediction for Cloud Services from The Past Usages - Praveen Kumar, G; Morarjee, K (International Journal of Computer Sciences and Engineering, 2014)
Web services are loosely-coupled software systems considered hold up interoperable machine-to-machine communication over a system. The most undemanding approach personalized cloud service quality of service ranking is to assess the entire service candidates at user side and position services base on observed values of quality of service. The materialization of web services has produces unprecedented prospect for organizations to setup additional agile as well as versatile collaborations with other organizations. Comparable to established component-based systems, cloud applications normally entail numerous cloud components that communicate over application programming interface. To attack this crucial challenge, we put forward a personalized ranking prediction structure, named cloud Rank to forecast quality of service ranking concerning a set of cloud services devoid of requiring extra real-world service invocations from the projected users. The target users of cloud rank structure are cloud applications, which require personalized cloud service ranking in support of building selection of optimal service.